A Personalized-based Study Guides Tool for Software Engineering Flipped Classes - Veras, Necio; Rocha, Lincoln; Viana, Windson (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2024: Anais do IV Simpósio Brasileiro de Educação em Computação, 2024)
Teaching Software Engineering (SE) poses challenges due to diverse levels of student knowledge. Active methods like Flipped Classrooms and Adaptive Learning can enhance SE learning. Flipped Classrooms involve pre-class study and in-class problem-solving, and Adaptive Learning tailors content to individual student needs. Our research mixes these approaches by introducing a personalized study guide tool. It’s a web-based platform for creating customized study guides for SE Flipped Classes. The tool adapts the guide content based on student’s performance and engagement. Within the tool, teachers set rules for content adaptation, focusing on class preparation and gaining insights into student progress. We evaluated the personalized study guides from three perspectives: perceptions, motivations, and achievements. The evaluation in a software requirements lesson with 22 students showed a significant improvement in scores and received positive feedback from students. Our tool has the potential to support the enhancement of SE education through personalized study guides in Flipped Classrooms.